Dietary protein utilization by fingerling of gamitana Colossoma macropomum, fed with isocaloric diets - Gutiérrez, Félix Walter (2010)
An experiment was conducted to examine effects of five levels of dietary protein (25, 27, 29, 31 y 33%) on performance by the gamitana, Colossoma macropomum Cuvier 1818. The parameters measured were weight gain (WG), food conversion (Fe), retained protein (RP), protein efficiency ratio (PER), and retained energy (RE). To prepare the experimental diets were used as protein sources anchovy meal and soybean meal, and as energy sources yellow corn, wheat bran and oil fish. Were found significant differences (P